PENERAPAN INTERVENSI BUERGER ALLEN EXERCISE PADA PASIEN DIABETES MELLITUS TIPE 2 DALAM MENGATASI MASALAH PERFUSI PERIFER TIDAK EFEKTIF: PENERAPAN INTERVENSI BUERGER ALLEN EXERCISE PADA PASIEN DIABETES MELLITUS TIPE 2 DALAM MENGATASI MASALAH PERFUSI PERIFER TIDAK EFEKTIF - Camelia, Dina; Roni, Faishol; Wijaya, Arif; Fitriyah, Erna Tsalatsatul; Amalia, Lulus Dian Ayu (LPPM STIKes Bahrul Ulum Jombang, 2022)
Diabetes mellitus is characterized by an increase in blood glucose levels. Patients with diabetes mellitus must perform self-care regularly to maintain normal blood glucose levels. High glucose levels will cause peripheral arterial disease (PAD) which usually affects the lower extremities. One way to prevent PAD is through physical exercise that involves the legs. The purpose of this scientific work is expected to be able to apply the Buerger Allen Exercise intervention in patients with type 2 diabetes mellitus in overcoming the problem of ineffective peripheral perfusion. This type of scientific research research is qualitative with a case study approach, the subjects used are two patients with ineffective peripheral perfusion nursing problems. The location of this research was in Arjosari Village, Pasuruan Regency, carried out for seven days every 15 minutes using data collection methods including assessment, determining diagnosis, intervention, implementation and evaluation. The results of the case study show that the Buerger Allen Exercise intervention can be used as physical exercise for people with type 2 diabetes mellitus at home. The conclusion from the results obtained related to the implementation of the Buerger Allen Exercise intervention in patients with type 2 diabetes mellitus can be proven by an increase in the Ankle Brachial Index value related to the Buerger Allen Exercise physical exercise.